Pengaruh Pertumbuhan Aset, Arus Kas Operasional, dan Kebijakan Dividen terhadap Kinerja Keuangan - Aat Sutihat; Indra Iman Sumantri; Syamsul Asmedi; Rizka Rismawati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The Consumer Non-Cyclicals sector plays a vital role in maintaining economic stability because it provides essential goods that remain in demand regardless of economic conditions. Nevertheless, companies in this sector are still required to maintain strong financial performance amid changing business environments, making it important to identify the factors that influence their performance. This study aims to analyze the effect of operating cash flow, dividend policy, and asset growth on the financial performance of Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The population consists of 87 companies, with a sample of 14 companies selected using purposive sampling. This research employs a quantitative approach using secondary data obtained from annual financial statements. Panel data regression analysis is applied to examine the simultaneous and partial effects of the independent variables on financial performance. The results indicate that dividend policy has a significant positive effect on financial performance, whereas operating cash flow and asset growth do not have a significant effect on financial performance.